Analisis Keterampilan Berkolaborasi Mahasiswa Rumpun Ilmu Sosial di Universitas Lampung - Pujiati Pujiati; Nurdin Nurdin; Wardani Wardani (Mahesa Research Center, 2022)
This study attempts to analyze skill collaborated students clumps social science at the University of Lampung. The research is descriptive quantitative research, done as a step seek solutions of the existing problems in the field namely less than optimal collaborative skills students in the global. Sample 206 determined some students active fill and restore instruments. Using techniques survey data collection. An analysis of data using descriptive quantitative. The results of the study are showing that as much as 62,349% students a clump of social science at the University of Lampung agree on the importance of skill collaborated. The most i really appreciate as much as the highest attitude 35,92% and the lowest in the group of individual accountability indicators 12,62%. Skill berkolabrosi should be owned by any student in order to prepare itself to entering the workforce. Skills/skills and knowledge shall be given birth to human resources who tough and skilled in accordance with the need the world of work. The ability of collaboration will form the readiness of the students in mastering the science in accordance its field, but will also form mentality and personality.